2018
DOI: 10.1186/s12885-018-4371-0
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, pattern and prognosis of brain metastases in patients with metastatic triple negative breast cancer

Abstract: BackgroundTo identify the incidence, recurrence pattern and prognosis of brain metastases (BM) among women with metastatic triple negative breast cancer (mTNBC) treated consecutively at a single institution during a 7-year period.MethodsPatients with histologically confirmed mTNBC were retrospectively identified. The incidence of BM as first site of recurrence and the cumulative BM incidence were computed. We used the Cox proportional hazards model to identify the univariate and multivariate factors associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
72
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(78 citation statements)
references
References 33 publications
5
72
0
1
Order By: Relevance
“…The incidence of brain metastasis was significantly higher with multiple sites of metastasis as compared to solitary site of metastasis. Our results match with other studies reporting higher risk of brain metastasis in patients with > 3 extra-cranial sites of involvement especially liver and bone [32,33]. In non-metastatic patient's recurrence increases the risk of brain metastasis also, as out of 448 non-metastatic patient's 57 patients relapsed later on and among them 26 (45.6%) developed brain metastasis.…”
Section: Discussionsupporting
confidence: 91%
“…The incidence of brain metastasis was significantly higher with multiple sites of metastasis as compared to solitary site of metastasis. Our results match with other studies reporting higher risk of brain metastasis in patients with > 3 extra-cranial sites of involvement especially liver and bone [32,33]. In non-metastatic patient's recurrence increases the risk of brain metastasis also, as out of 448 non-metastatic patient's 57 patients relapsed later on and among them 26 (45.6%) developed brain metastasis.…”
Section: Discussionsupporting
confidence: 91%
“…A study in two major institutions [27] in carcinoid patients with bone and/or liver metastases confirmed that coexistence of bone and liver metastasis was indicative of worse prognosis with a significant difference in overall survival -the small total numbers of patients (691) might have made it more difficult to obtain statistical significance in other histologies. The poor prognosis of brain metastases is not unexpected and is consistent across different tumor types, such as breast [28,29], lung [30], gastrointestinal [31] and ovarian [32]. It is usually measured in matters of months and may reflect the virulence of the tumor, the severity of CNS dysfunction or the inability of most current therapies to cross the blood brain barrier.…”
Section: Discussionmentioning
confidence: 99%
“…Around 25% of BC cases show HER2 amplification, and out of these, 30-55% of patients develop BM with a median survival of only 4-14 months [5,6]. Furthermore, TNBC patients with ER -/PR -/ HER2status are at high risk of BM recurrence [7].…”
Section: Introductionmentioning
confidence: 99%